THE EFFECT OF CORN BRAN REPLACEMENT IN COMPLETE FEED WITH FERMENTED BREAD WASTE FLOUR ON THE APPEARANCE OF MALE BALI DUCKS (Anas sp.) AGED 0-8 WEEKS - M. Y. P., Wedaswara; Siti, N. W.; Candrawati, D. P. M. A. (Jurnal Peternakan Tropika; Vol 9 No 2 (2021): Vol. 9 No. 2 Tahun 2021; May - August, 2021)
This study aims to determine the effect of replacing corn bran in complete feed with fermented bread waste flour on the appearance of male bali ducks ( Anas Sp. ) aged 0-8 weeks. This research was conducted at the Farm Faculty of Animal Husbandry, Udayana University, which is located on Sesetan street Markisa alley no 5, Sesetan Village, South Denpasar District, Denpasar City, Bali, for 8 weeks. The design used was a completely randomized design (CRD) with 3 treatments and 5 replications, so there were 15 experimental units. Each experimental unit used 3 male bali ducks ( Anas Sp. ) with a weight range of 50 ± 2 grams. The three treatments were male bali ducks ( Anas Sp. ) which were given complete feed treatment without bread waste (treatment A), male bali ducks ( Anas sp. ) which were given 50% waste of bread instead of corn bran (treatment B), and bali ducks. Male ( Anas Sp. ) treated with complete feed + 100% bread waste substitute for corn bran (treatment C). The variables observed included initial body weight, final body weight, weight gain, ration consumption and Feed Conversion Ratio (FCR). In general, the appearance of male bali ducks ( Anas Sp. ) treated (B) and (C) tended to be significantly higher (P<0.05) in final body weight, weight gain, and FCR were not significantly different ( P>0.05) compared to treatment (A). Based on the results of this study, it can be concluded that male bali ducks ( Anas Sp. ) treated with complete feed + 50% bread waste (B) and male bali ducks ( Anas Sp. ) treated with complete feed + 100% bread waste can improved appearance of the male bali duck ( Anas Sp. ) aged 0-8 weeks. Keywords : male bali duck (Anas Sp.), appearance, bread waste